A modeling study of the response of Asian summertime climate to the largest geologic forcings of the past 50 Ma. Issue 10 (25th May 2016) - Roe, Gerard H.; Ding, Qinghua; Battisti, David S.; Molnar, Peter; Clark, Marin K.; Garzione, Carmala N.
Abstract: The modern Asian summer monsoon is known to be affected by the modern continental geometry, orography, atmospheric composition, interglacial climate state, and orbital configuration. All of these factors, however, have undergone substantial changes since the Indian and Asian continents collided 50 million years ago. Within the framework of one general circulation model we evaluate the relative importance of each of these factors for the spatial patterns of summertime climate fields and precipitation‐weighted 18 O. We find that the continental‐scale structure of the monsoon circulation remains robust, but there are important impacts on local environmental conditions. The largest differences in climate are associated with changes in orbital configuration and topography because of how those factors influence local gradients in the summer climate variables. Finally, model calculations are consistent with the modern understanding of monsoon dynamics in which the strength of the circulation and the distribution of rainfall are tightly coupled to the spatial patterns of low‐level moist static energy and upper tropospheric temperature. Key Points: Geological changes in the Cenozoic have changed summertime climate in Asia The continental‐scale structure of the summer monsoon circulation remains robust Large local climate changes occur, with insolation and local topography having the largest impacts